(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Stem cells are unique cells that can differentiate into various cell types, making them a valuable tool in regenerative medicine. Stem cells can be obtained from various sources, including embryonic tissue, fetal tissue, adult tissue, and induced pluripotent stem cells (iPSCs). Stem cells can be obtained from different sources, like bone marrow, peripheral blood, umbilical cord blood, adipose tissue and dental pulp. Each with its advantages and disadvantages. The choice of source for stem cell extraction depends on the type of cells required, the quantity needed, and the patient's medical condition. Further research is needed to optimize the extraction and isolation of stem cells from different sources and to determine their efficacy in treating various diseases and conditions. Regenerative medicine researchers are exploring ways to use stem cells to replace damaged cells or tissues that cannot be regenerated naturally by the body. This approach holds great promise for treating a range of diseases and injuries, including heart disease, spinal cord injuries, and diabetes.